Exploring the role of translanguaging in linguistic ideological and attitudinal reconfigurations in the Spanish classroom for heritage speakers. Issue 3 (2nd October 2019) - Prada, Josh
ABSTRACT: The present study explores how translanguaging serves as vehicle to (help) re-configure linguistic attitudinal and ideological structures in a university Spanish course for heritage speakers. Specifically, it focuses on the links between exposure to (and engagement in) classroom translanguaging and the participants' challenging of traditional monoglossic ideologies governing folk imaginary regarding language purity, standard, and appropriate academic discourse. Three class meetings worth of classroom ethnographic observations (among 17 students), and eight semi-structured individual interviews were transcribed and analysed via directed qualitative analysis. Departing from four predetermined categories (i.e. language attitudes, language ideologies, belief change, and translanguaging instances) the linguistic attitudinal and ideological dynamics among the participants were investigated. Results are weaved into a narrative which evolves around three main categories: (1) language attitudes and ideologies prior to entering the classroom, (2) attitudinal and ideological changes and their link to translanguaging, and (3) considerations about translanguaging in academic settings and academic discourse. Findings unveil a double-action whereby translanguaging creates a sociolinguistic frame that challenges widely held linguistic attitudes and ideologies about the nature of flexible linguistic practices, as it stimulates their normalization and inclusion in a context that has traditionally been closed to such practices.